1999
DOI: 10.1099/13500872-145-3-673
|View full text |Cite
|
Sign up to set email alerts
|

Porin expression in clinical isolates of Klebsiella pneumoniae

Abstract: Two porins, OmpK36 and OmpK35, have been described previously in Klebsiella pneumoniae, and they are homologous to the Escherichia coli porins OmpC and OmpF, respectively, at both the DNA and amino acid levels. Optimal resolution of the two K. pneumoniae porins by electrophoresis on polyacrylamide gels is not achieved using gel systems already described for E. coli and requires modifications of the bisacrylamide content of the resolving gels. Once resolved, identification of porins OmpK36 and OmpK35 cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 40 publications
12
148
0
1
Order By: Relevance
“…Those patients had several co-morbidities and were subjected to aggressive medical interventions, including broad-spectrum antibiotics. These results are in agreement with previously reported findings that showed that prior antimicrobial exposure in hospitalised patients, especially severely ill patients, is the main force driving the spread of carbapenem-resistant organisms (Hernandez-Alles et al, 1999;Hoenigl et al, 2012;Patel et al, 2008;Souli et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Those patients had several co-morbidities and were subjected to aggressive medical interventions, including broad-spectrum antibiotics. These results are in agreement with previously reported findings that showed that prior antimicrobial exposure in hospitalised patients, especially severely ill patients, is the main force driving the spread of carbapenem-resistant organisms (Hernandez-Alles et al, 1999;Hoenigl et al, 2012;Patel et al, 2008;Souli et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…OM proteins were extracted from each strain grown in 20-mL LB medium or nutrient broth (NB) broth with sodium lauroyl sarcosinate (Sigma-Aldrich) and recovered by ultracentrifugation, as described previously. 44 Samples were separated by 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and stained with Coomassie brilliant blue R250 (Gibco-BRL). For protein gel blots, proteins were separated using 12% SDS-PAGE and blotted to a Hybond-C membrane (Amersham), probed with polyclonal antibodies raised against YfgL, and revealed with peroxidase-labeled goat anti-rabbit antibody and the enhanced chemiluminescent substrate.…”
Section: Methodsmentioning
confidence: 99%
“…OmpF is highly expressed at low osmolarity and suppressed at high osmolarity, while OmpC is totally the opposite (Cai and Inouye, 2002). More and more similar regulations have been found in other bacteria, such as major outer membrane protein and Omp50 in Campylobacter jejuni (Dedieu et al, 2002), and OmpK35 and OmpK36 in Klebsiella pneumoniae (Hernandez-Alles et al, 1999). Furthermore, Wu et al (2006) indicated that OmpW and OmpV are required for environmental salt regulation in Photobacterium damsela, in which OmpW and OmpV, respectively, elevate and reduce the ability in salinity tolerance.…”
Section: Introductionmentioning
confidence: 72%